Special papersDiagnostic and therapeutic advances in dermatomyositis - Samotij, Dominik; Szczęch, Justyna; Reich, Adam (Dermatology Review/Przegląd Dermatologiczny, 2015)
Dermatomyositis (DM) is one of the so-called idiopathic inflammatory myopathies (IIM). Dermatomyositis is an autoimmune disorder characterized by the presence of cutaneous lesions and/or symptoms of muscle involvement with the following variants: the “classic” variant of DM, juvenile DM, paraneoplastic DM, drug-induced DM and amyopathic DM. Dynamic discoveries of novel autoantibodies, including anti-TIF1, anti-NXP2, anti-SAE or anti-MDA5, related to certain DM variants, have been described in recent years. It seems that these antibodies will contribute to better recognition of DM and its particular variants, a better risk stratification for predicting internal organ involvement, and to a global improvement of treatment outcome. Corticosteroids remain the mainstay of DM therapy, but new immunomodulatory and immunosuppressive agents, including biologicals, resulted in a significant increase of the survival rate of DM patients. Here, we review the current literature data on DM with special emphasis on new trends in its diagnostics and treatment.